2018
DOI: 10.1038/s41598-018-24305-2
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of the yeast mitochondrial lipidome and associated membrane proteins following heterologous expression of Artemia-ANT

Abstract: Heterologous expression is a landmark technique for studying a protein itself or its effect on the expression host, in which membrane-embedded proteins are a common choice. Yet, the impact of inserting a foreign protein to the lipid environment of host membranes, has never been addressed. Here we demonstrated that heterologous expression of the Artemia franciscana adenine nucleotide translocase (ANT) in yeasts altered lipidomic composition of their inner mitochondrial membranes. Along with this, activities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…The abundance of DAG was found to be rather high with 25% of the analyzed PLs, possibly indicating a co-purification of mitochondria-attached ER or lipid droplets. Nevertheless, the amount of DAG is comparable to previous observations in highly purified yeast mitochondria [46], which is why we expected the quality of the isolated mitochondrial fractions to be sufficient for further experiments. Surprisingly, we detected only low amounts of the mitochondrial signature PL cardiolipin (1.5%), which, in other species like yeast, mammals or plants, represents 10-15% of mitochondrial PLs [47].…”
Section: Unravelling Age-dependent Alterations In the Mitochondrial Lipid Composition Of P Anserinasupporting
confidence: 80%
“…The abundance of DAG was found to be rather high with 25% of the analyzed PLs, possibly indicating a co-purification of mitochondria-attached ER or lipid droplets. Nevertheless, the amount of DAG is comparable to previous observations in highly purified yeast mitochondria [46], which is why we expected the quality of the isolated mitochondrial fractions to be sufficient for further experiments. Surprisingly, we detected only low amounts of the mitochondrial signature PL cardiolipin (1.5%), which, in other species like yeast, mammals or plants, represents 10-15% of mitochondrial PLs [47].…”
Section: Unravelling Age-dependent Alterations In the Mitochondrial Lipid Composition Of P Anserinasupporting
confidence: 80%
“…1 B ) ( 17 ) and are thus expected to influence membrane protein function. Previous work has shown that heterologous expression of membrane proteins in yeast can itself perturb the phospholipid composition ( 20 ), which can confound our study. Therefore, we first tested the effect of expressing MCU on the phospholipid composition of WT yeast cells.…”
Section: Resultsmentioning
confidence: 99%
“…1B) (17) and are thus expected to influence membrane protein function. Previous work has shown that heterologous expression of membrane proteins in yeast can itself perturb the phospholipid composition (20), which can confound our study. Therefore, we first tested the effect of expressing MCU on the phospholipid composition of WT yeast cells.…”
Section: Resultsmentioning
confidence: 99%